Diversity of urban growth patterns in Sub-Saharan Africa in the 1960–2010 period. Issue 1 (2nd January 2020) - Wolff, Eléonore; Grippa, Taïs; Forget, Yann; Georganos, Stefanos; Vanhuysse, Sabine; Shimoni, Michal; Linard, Catherine
ABSTRACT: Since 1960, urbanization in Sub-Saharan Africa (SSA) has been rapid. While consistent demographic statistics now exist on urban population growth rates, these data have not been fully exploited to improve our understanding of the evolution of urbanization at the continental scale. We investigate urban change between 1950 and 2010 across SSA using cluster analyses performed on three complementary aspects: the evolution of urban growth rates, primacy, and the densification of the urban mesh. Results show that SSA countries followed diverse urbanization trajectories over the last 60 years and are currently unevenly distributed along the urban transition model.